Chemically diverse activity-based probes with unexpected inhibitory mechanisms targeting trypsin-like serine proteases - Ramos-Llorca, Alba; Decraecker, Lisse; Cacheux, Valérie M. Y.; Zeiburlina, Irena; De bruyn, Michelle; Battut, Louise; Moreno-Cinos, Carlos; Ceradini, Davide; Espinosa, Eric; Dietrich, Gilles; Berg, Maya; De Meester, Ingrid; et al. (Frontiers in Chemistry, 2023)
Activity-based probes (ABP) are molecules that bind covalently to the active form of an enzyme family, making them an attractive tool for target and biomarker identification and drug discovery. The present study describes the synthesis and biochemical characterization of novel ABPs targeting trypsin-like serine proteases. We developed an extensive library of ABPs with “clickable” affinity tags and a diaryl phosphonate warhead. A wide diversity was achieved by including natural amino acid analogs as well as basic polar residues as side chains. A detailed enzymatic characterization was performed in a panel of trypsin-like serine proteases. Their inhibitory potencies and kinetic profile were examined, and their IC50 values, mechanism of inhibition, and kinetic constants were determined. The ABPs with a benzyl guanidine side chain showed the highest inhibitory effects in the panel. Surprisingly, some of the high-affinity probes presented a reversible inhibitory mechanism. On the other hand, probes with different side chains exhibited the expected irreversible mechanism. For the first time, we demonstrate that not only irreversible probes but also reversible probes can tightly label recombinant proteases and proteases released from human mast cells. Even under denaturing SDS-PAGE conditions, reversible slow-tight-binding probes can label proteases due to the formation of high-affinity complexes and slow dissociation rates. This unexpected finding will transform the view on the required irreversible nature of ABPs. The diversity of this library of ABPs combined with a detailed enzyme kinetic characterization will advance their applications in proteomic studies and drug discovery.